Family Violence, Sibling, and Peer Aggression During Adolescence: Associations With Behavioral Health Outcomes - Ingram, Katherine M.; Espelage, Dorothy L.; Davis, Jordan P.; Merrin, Gabriel J. (Frontiers in Psychiatry, 2020)
Bullying and sibling aggression include similar behaviors, though the latter is comparatively understudied. Aligned with the Theory of Intergenerational Transmission of Violence, research suggests that exposure to family violence increases an individual’s risk for perpetrating violence in their own future relationships. Additionally, Problem Behavior Theory suggests that engaging in one problem behavior (e.g., bullying) increases the likelihood of engaging in other problem behaviors (e.g., substance use). In Phase 1, this study of middle school students from the U.S. (N = 894, sampled from 4 middle schools) examined how exposure to family violence predicted membership in latent classes of bullying and sibling aggression perpetration. In Phase 2, we used mixture modeling to understand how latent classes of family violence, sibling aggression, and bullying predict future substance use, mental health outcomes, and deviance behavior later. In high school. Results yielded four profiles of peer and sibling aggression: high all, high sibling aggression, high peer aggression, and low all aggression. Youth who reported witnessing more family violence at home were significantly more likely to fall into the sibling aggression only and high all classes, compared to the low all class. Phase 2 results also yielded four classes: a high all class, a sibling aggression and family violence class, a peer aggression class, and a low all class. Individuals in the high all class were more likely to experience many deleterious outcomes (substance use, depression, delinquency) compared to other classes. This study provides evidence for pathways from witnessing violence, to perpetrating aggression across multiple contexts, to developing other deleterious mental and behavioral health outcomes. These findings highlight the deleterious impact of family violence on child development, providing support for a cross-contextual approach for programming aimed at developing relationships skills.